Identify Components of Bureauphobia Attitude in Qom Hospitals (With Qualitative Research Approach) - Hossein Azari; Habib Roodsaz; Behrouz Rezaei Manesh; Mir Ali Seyed Naghavi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2022)
Background and Objectives: Studies in various fields of healthcare seeks to gain the trust of citizens by providing more favorable services. Despite the generality of this view, Bureauphobia as a new attitude in the field of behavior, questioned these studies. The current study aims to identify the components of bureauphobia in in people referred to public hospitals in Qom, Iran. Methods: This is a qualitative study using thematic analysis. The study population consists of all people referred to public Hospitals in Qom province. Of these, 190 were selected and interviewed. The interview transcribes were analyzed in three stages: descriptive coding, interpretive coding, and identifying main themes. Results: The analysis led to the formation of 131 descriptive codes, 50 interpretive codes and 10 main themes. The results showed that direct experiences, personality, role/ example, the political system governing public bureaucracy, social capital, malfunction of the bureaucracy, intrinsic features of the public sector, moneyism, moral values, and social justice were the components of bureauphobia. Conclusion: People with bureauphobia have a pessimistic view. Satisfaction with the services provided by public hospitals does not necessarily lead to trust in these centers. Some people are constantly exposed to negative opinions about public hospitals; hence, their attitudes towards public hospitals are negative and biased.